Farmers’ Perception on the Establishment of Knowledge Centres in Coastal and Tribal Areas of Gujarat - P. Mahalakshmi, C. Gopal, M. Muralidhar, Prem Kumar, P.K. Patil, M. Kailasam, H.G. Solanki, R.V. Borichangar; J.G. Vanza (Indian Journal of Extension Education, 2018)
This study was undertaken in Gujarat to analyse the farmers’ perception on the establishment of knowledge centres in coastal and tribal areas. Among the various services, all the respondents needed details on the aquaculture practices, market pricing, and e-mail/internet facilities in the centre for upgrading their knowledge in aquaculture and better communication among the fellow farmers and experts respectively. Farmers strongly agreed that the knowledge centre is necessary for coastal and tribal development. It is also essential for getting information quickly and useful for decision making in cultural practices. The respondents ranked unity among the village people as the major challenge for implementation of the centre with a rank-based quotient of 89.58 followed by the requirement of sustainability in both content and finance (85%) and interest in usage of advance technologies like computer, internet etc. among the farmers (83.33%). Adequate training should be given to the farmers are also suggested for better utilization of ICT tools. The training in advanced technology helps the farmers to increase their efficiency and profitability of aquaculture production. Overall opinion for the establishment of centre and the improvement of the initiatives are also discussed.